2020
DOI: 10.1371/journal.pone.0231426
|View full text |Cite|
|
Sign up to set email alerts
|

Impacts of plant growth promoters and plant growth regulators on rainfed agriculture

Abstract: Demand for agricultural crop continues to escalate in response to increasing population and damage of prime cropland for cultivation. Research interest is diverted to utilize soils with marginal plant production. Moisture stress has negative impact on crop growth and productivity. The plant growth promoting rhizobacteria (PGPR) and plant growth regulators (PGR) are vital for plant developmental process under moisture stress. The current study was carried out to investigate the effect of PGPR and PGRs (Salicyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 95 publications
5
76
0
1
Order By: Relevance
“…The proteins include aquaporins, heat shock proteins, and late embryogenesis abundant proteins, whereas the amino acids include proline and glycine betaine [52]. Khan et al [53] indicated that foliar spray of Bacillus subtilis, Bacillus thuringiensis, and B. megaterium in pot experiment enhanced the leaf protein and sugar content in drought-sensitive chickpea plants under moisture stress.…”
Section: F I G U R Ementioning
confidence: 99%
“…The proteins include aquaporins, heat shock proteins, and late embryogenesis abundant proteins, whereas the amino acids include proline and glycine betaine [52]. Khan et al [53] indicated that foliar spray of Bacillus subtilis, Bacillus thuringiensis, and B. megaterium in pot experiment enhanced the leaf protein and sugar content in drought-sensitive chickpea plants under moisture stress.…”
Section: F I G U R Ementioning
confidence: 99%
“…Under stress conditions, PGPR can improve the injurious impacts and enhance the yield production under salt conditions [45], as a bio-fertilizer in sugar beet and sweet sorghum plants [20,46,47] and as a bio-control agent [48][49][50]. There are many PGPR strains, such as Bacillus, Azotobacter, Azospirillum, Pseudomonas, Rhizobium, and Serratia, which can be used in improving plant growth even under various stress factors [51,52] by the production of antioxidants, phytohormones and vitamins [53]. There is a lot of information about the effect of PGPR, nevertheless studies about chitosan and its effects on plants under salinity stress are still scarce and have not yet been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Along with chemicals, microbiological preparations are also used: rizoplan, trichodermin, agate 25, pseudobacterin, etc. [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%